Mining Technologies Innovative Development II (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The success of mining innovative development, as a part of the global transition to sustainable development, is determined by interdisciplinary research that combines innovations in the extraction of traditional fossil fuels, the production of energy from alternative sources, both in geophysics and geochemistry, and information technology. Therefore, the papers collated here contribute to the transition of mining to the circle of sectoral leaders in innovative development.